2019
DOI: 10.1016/j.envres.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential carcinogenicity of organic chemicals in synthetic turf crumb rubber

Abstract: Currently, there are > 11,000 synthetic turf athletic fields in the United States and > 13,000 in Europe. Concerns have been raised about exposure to carcinogenic chemicals resulting from contact with synthetic turf fields, particularly the infill material (“crumb rubber”), which is commonly fabricated from recycled tires. However, exposure data are scant, and the limited existing exposure studies have focused on a small subset of crumb rubber components. Our objective was to evaluate the carcinogenic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 22 publications
(21 reference statements)
0
35
0
2
Order By: Relevance
“…4−6 In addition to PAHs, multiple chemical additives have been reported to be present in rubber granulates such as benzothiazoles, phthalates, metals, and bisphenol A. 4−6 A recent literature review by Perkins et al, 7 identified 306 chemical constituents of rubber granulate used as infill material in synthetic turf athletic fields. No information was provided on the prevalence of chlorinated paraffins (CPs).…”
Section: Introductionmentioning
confidence: 99%
“…4−6 In addition to PAHs, multiple chemical additives have been reported to be present in rubber granulates such as benzothiazoles, phthalates, metals, and bisphenol A. 4−6 A recent literature review by Perkins et al, 7 identified 306 chemical constituents of rubber granulate used as infill material in synthetic turf athletic fields. No information was provided on the prevalence of chlorinated paraffins (CPs).…”
Section: Introductionmentioning
confidence: 99%
“…According to results from researchers in China, they have found between 131,019 m 3 and 146,783 m 3 of soil contaminated with benzo [a] pyrene; it should be mentioned that pollutants are accumulated mainly in the first layer of the site (0-1 meter) [37]. Its main impact on human health is centered on its genotoxic properties (teratogenic, mutagenic, and carcinogenic) (Figure 1) [38].…”
Section: Soils Contaminated By Hydrocarbonsmentioning
confidence: 99%
“…While information is known about tire manufacturing, many variables are unknown, including persistence of byproducts, chemical changes during vulcanization, and adsorption of environmental chemicals, which might affect the chemical composition of the ultimate crumb rubber product. A recent literature review of crumb rubber chemical characterization studies outlines some chemicals of concern; using ADMET Predictor™, this study identified 197 predicted carcinogens, of which 52 have been previously classified as carcinogens by the U.S. Environmental Protection Agency (EPA) or European Chemicals Agency (ECHA) 1 . Other chemicals of concern as well as more information about crumb rubber manufacturing and synthetic turf construction and standards, are described in the 2016 EPA Federal Research Action Plan 2 .…”
Section: Introductionmentioning
confidence: 99%